Chitty on contracts - Beale, H. G. (Sweet & Maxwell, 2004)
The undisputed heavyweight of contract law, Chitty on Contracts, is now in its 29th edition. Since it was first published in 1826, it has grown in stature and authority with every new edition. Its two volumes provide unrivalled expertise for common law and commercial barristers and solicitors as well as academics and the judiciary internationally. Chitty's clear written style ensures it can be read and understood by practitioners at all levels of expertise within contract law. Interpretation and explanatory narrative are supported by examples of case law and legislation. Volume I covers General Principles, whilst Volume II deals with Specific Contracts. All the latest key developments in case law and legislation since the 28th edition in 1999 have been incorporated into this edition. The work is supplemented regularly to ensure it remains relevant and authoritative. Of particular note is the inclusion of recent legislation such as: * The Financial Services and Markets Act 2000 * The Consumer Protection (Distance Selling) Regulations 2000 * The Enterprise Act 2002 * The Employment Act 2002 Chitty is available in two volumes, but there is also the option available to purchase Volume One separately.